Implementation of Contextual Teaching and Learning Model in Nature-Based Learning to Improve Morals and Concern for the School Environment at SMP S Alam Leuser - Safri, Zainal; Hasanah, Siti; Mahmudah; Soraya, Fitri; Siregar, Tuti Sriwahyuni (Jurnal Profesi Guru Indonesia, 2024)
This classroom action research examines the implementation of the Contextual Teaching and Learning (CTL) model in nature-based learning to enhance students' morals and environmental awareness at SMP S Alam Leuser. The study aims to determine how CTL strategies, which emphasize meaningful and experiential learning, can foster students’ ethical values and ecological responsibility. Conducted in two cycles, this research follows the Kemmis and McTaggart action research model, consisting of planning, action, observation, and reflection. Data were collected through observations, student reflections, teacher journals, and interviews. The findings indicate that integrating CTL with nature-based learning significantly improves students’ moral values, such as honesty, responsibility, and cooperation. Furthermore, students demonstrate increased environmental awareness through active participation in sustainable practices, including waste management, tree planting, and water conservation efforts. Each cycle of the research reveals progressive improvement in student engagement and behavioral changes, emphasizing the role of contextual learning in character building. The study highlights the importance of teacher facilitation in connecting learning materials to real-life environmental issues, making the learning process more relevant and impactful. The results suggest that CTL-based nature learning is an effective pedagogical approach for developing both cognitive and affective competencies in students. This study recommends further exploration of CTL implementation in various educational settings to assess its broader impact on student character development and environmental consciousness.